Are women leaders significantly better at controlling the contagion during the COVID-19 pandemic? - Maxwell SALVATORE; Bhramar MUKHERJEE (Journal of Health and Social Sciences)
Introduction: Recent media articles have suggested that women-led countries are doing better in terms of their responses to the COVID-19 pandemic. The aim of this paper is to examine an ensemble of public he- alth metrics to assess the control of COVID-19 epidemic in women- versus men-led countries worldwide based on data available up to June 3. Methods: We restrict our analysis to 159 countries with at least 100 cumulative reported cases of CO- VID-19 infections and at least 10 days of reported data as of June 3, 2020. We compared in women- versus men-led countries the trajectory of time varying reproduction number R(t) as well as most recent values of R(t) and other metrics of viral transmission such as doubling time and case-fatality rates. A two-sample bootstrap procedure-based comparison of medians and construct 95% confidence interval (95% CI) based on empirical 2.5th and 97.5th percentile of the bootstrap distributions were used. Results: The median of the distribution of median time-varying effective reproduction number for women- and men-led countries were 0.89 and 1.14 respectively with the 95% two-sample bootstrap-based confiden- ce interval for the difference (women - men) being -0.34 to 0.02. In terms of scale of testing, the median percentage of population tested were 3.28% (women), 1.59% (men) [95% CI -1.29% to 3.60%)] with test positive rates of 2.69% (women) and 4.94% (men) respectively. Conclusion: It appears that though statistically not significant, countries led by women have an edge over countries led by men in terms of public health metrics for controlling the spread of the COVID-19 pan- demic worldwide.